The development of mobile logistic support in Anglo-American naval policy, 1900-1953 - Nash, Peter V. (New perspectives on maritime history and nautical archaeology., 2009)
Compares the methods the British and American navies developed to supply their ships across the vast reaches of the Pacific Ocean during the first part of the twentieth century.